Manajemen Konflik Sengketa Tanah Di Desa Karueng Kecamatan Enrekang Kabupaten Enrekang - Nasir, Nirmayani; Usman, Jaelan; Muhiddin, Amir (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study was to find out the Conflict Management which focused on Land Dispute Conflict Management in Karueng Village, Enrekang District, Enrekang Regency. This study used qualitative research with descriptive research type. The results showed that the Land Dispute Conflict Management in Karueng Village, Enrekang District, in the process of solving problems that occurred using the negotiation method and the mediation method. Apart from the Karueng Village Head who participated in the mediation process, the Head of Karueng Village and the Enrekang Sector Police also participated in the mediation process. The results of the mediation process carried out in the form of peace between the two parties and there were also cases of disputes that had not found a solution, so the problem was under the law. Conciliation and arbitration methods had never used in resolving land disputes in Karueng Village.Keywords: Conflict Management, Land Dispute